2018
DOI: 10.1016/j.molliq.2018.08.161
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on CNT nanofluids behavior in laminar pipe flow

Abstract: This paper numerically investigates the heat transfer behavior of carbon nanotubes nanofluids under laminar forced flow in horizontal pipe. In order to describe better the nanofluids flow, the thermophysical properties were previously experimentally evaluated considering the influence of nanoparticle content and the effect of non-Newtonian nature of some nanofluids. In an original manner, this study was conceived considering a real experimental setup with known boundary conditions for simulation validation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…90'lı yılların ortalarında nanometre boyutundaki katı partiküllerin bir baz akışkan içerisindeki süspansiyonu Choi ve Eastman [3] tarafından nanoakışkan olarak adlandırılmıştır. 20. yüzyılın ikinci yarısından itibaren ısı transferinin iyileştirilmesinde konvansiyonel iş akışkanlarına alternatif olabileceği için nanoakışkanlar, bilim insanlarının ilgisini çekmiş ve popüler araştırma konuları arasındaki yerini almıştır [4]. Nanoakışkan kavramının ortaya atılmasından itibaren en genel halde nanoakışkanların hazırlanması, termofiziksel ve reolojik özelliklerinin belirlenmesi, çeşitli mühendislik uygulamalarında konvansiyonel iş akışkanlarına göre performanslarının kıyaslanması ve kararlılıkları konularında sayısal ve deneysel çalışmalar yapılagelmektedir [5].…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…90'lı yılların ortalarında nanometre boyutundaki katı partiküllerin bir baz akışkan içerisindeki süspansiyonu Choi ve Eastman [3] tarafından nanoakışkan olarak adlandırılmıştır. 20. yüzyılın ikinci yarısından itibaren ısı transferinin iyileştirilmesinde konvansiyonel iş akışkanlarına alternatif olabileceği için nanoakışkanlar, bilim insanlarının ilgisini çekmiş ve popüler araştırma konuları arasındaki yerini almıştır [4]. Nanoakışkan kavramının ortaya atılmasından itibaren en genel halde nanoakışkanların hazırlanması, termofiziksel ve reolojik özelliklerinin belirlenmesi, çeşitli mühendislik uygulamalarında konvansiyonel iş akışkanlarına göre performanslarının kıyaslanması ve kararlılıkları konularında sayısal ve deneysel çalışmalar yapılagelmektedir [5].…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…They founded that the Nusselt number of nanofluids is decreased with the increase of the volume fraction of nanofluid, which is related to non-Newtonian behavior of nanofluids. Minea and Estellé [23] carried out a numerical study of the heat transfer behavior of carbon nanotubes nanofluids under laminar forced flow in horizontal pipe. They evidenced that the convective heat transfer coefficient of nanofluid is better for low Re number and higher nanoparticles volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the CFD can predict the convection features using the nanofluid as heat transfer fluid. Many different particles can be used in applications, but in recent years the use of highly conducive carbon nanotubes (CNTs) is growing [46][47][48][49][50]. They provide significant heat transfer enhancements [51][52][53].…”
Section: Introductionmentioning
confidence: 99%